Contamination characteristics, source analysis, and ecological risk assessment of toxic metals and metalloid in agricultural soil in Yuzhong, China. Issue 1 (1st December 2020) - Duan, Kaixiang; Zhao, Baowei; Zhang, Songlin; Ma, Yanlong
Abstract: Human activities have caused toxic metal pollution and ecological risks to agricultural soil. In this study, 291 topsoil samples, collected in the agricultural soil system of Yuzhong, China, were selected to study the toxic metals and metalloids contamination characteristics, source and ecological risk based on geostatistics, pollution index, and ecological risk index. The main distribution of As is adjacent to pasture land and mainly comes from animal husbandry; Pb was observed near a coal mining factory and the Yellow River and was derived from industry and transportation; Cd was similar to Pb and was mainly derived from industry, transportation, and agriculture; Cr was found near a cement plant and was derived from industry and transportation; and Hg was found near an urban area and was mainly from industry and domestic garbage. The ratio of these elements exceeding the soil background value reached 99.9%. Except for the excess amounts of Cd and Hg in some samples, Cr, Hg, and As were mostly below permissible limits. Moreover,  the comprehensive potential ecological risk of toxic metals is mainly at medium level and below, whereas the risks of Cd and Hg are higher. Control of Cd and Hg is important to prevent soil pollution. This study explains the current contamination situation, the predominant contaminants and their sources, and provides emphasis and direction for agricultural soil remediation. Core Ideas: Analysis combined with nutrients can help explain the sources of toxic metals and metalloid. The main anthropogenic pollution sources of toxic metals and metalloid are varied. Most (99.9%) toxic metals and metalloid concentrations exceeded their background value. The potential ecological risks of Cd and Hg are severe.